Development of Functional Prebiotic Nutraceutical Supplement Mix for Geriatrics: Life Sciences-Food Technology - V, Nandha Kumar; R, Ragul; S, Saran Kumar; Balamurugan P, Dr (International Journal of Life Science and Pharma Research, 2023)
This study aims to develop a functional prebiotic nutraceutical supplement mix for geriatrics and evaluate its nutritional and sensory characteristics. Prebiotics are non-digestible food nutrients that selectively stimulate the activities of beneficial probiotic organisms in the colon and maintain intestinal microbial balance. Nutraceutical includes functional foods, dietary supplements, and medical foods. Geriatrics is a medical practice that addresses older patients' complex needs and maintains functional independence even in the presence of chronic diseases. Elderly people are at risk for macro and micronutrient deficiencies due to various social, physical, and economic obstacles. This research product aims to promote the ideal blend of grains, legumes, and nuts for elderly people and enhance their nutritional energy. Foxtail millets, oats, garlic, almonds & cashew nuts possess high prebiotic content. This study formulated ten formulations using Response Surface Method – Design Expert 12.0. The third sample (Trial 3) containing foxtail millet (25%), green pea protein isolate (10%), oats (15%) and carrot (15%), pomegranate (15%), garlic (5%), almond & cashew nut (5%), skim milk solids (10%) had the highest score for sensory attributes. The developed combination was high in nutrients and provide ample protein and energy for daily needs. Its nutritional value for 100g is of total protein (11.5%), fat (4.36), carbohydrate (67.57), vitamins, minerals, and total energy (360.17 K/Cal).